2015
DOI: 10.1016/j.brq.2014.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of radio spokesperson's gender, vocal pitch and accent and the use of music in radio advertising

Abstract: The aim of this study is to analyze how certain voice features of radio spokespersons and background music influence the advertising effectiveness of a radio spot from the cognitive, affective and conative perspectives. We used a 2 x 2 x 2 x 2 experimental design in 16 different radio programs in which an ad hoc radio spot was inserted during advertising block. This ad changed according to combinations of spokesperson's gender (male–female), vocal pitch (low–high) and accent (local–standard). In addition to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 44 publications
3
15
1
1
Order By: Relevance
“…The presentation of appeal drivers in the advertisement may draw consumers' attention towards advertisement, which may ultimately impact their consumption patterns (Zeitlin and Westwood, 1986). The impact of advertising music, message, picture quality, and color appeal drivers on women's responses has been researched by academic scholars in various fields (Park and Young, 1986;Martin-Santana et al, 2015;Stoeckel et al, 2007;Lichtlé, 2007). The majority of such research shows the positive response of women towards those adverts which incorporate emotional appeal drivers while developing the advertisements.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The presentation of appeal drivers in the advertisement may draw consumers' attention towards advertisement, which may ultimately impact their consumption patterns (Zeitlin and Westwood, 1986). The impact of advertising music, message, picture quality, and color appeal drivers on women's responses has been researched by academic scholars in various fields (Park and Young, 1986;Martin-Santana et al, 2015;Stoeckel et al, 2007;Lichtlé, 2007). The majority of such research shows the positive response of women towards those adverts which incorporate emotional appeal drivers while developing the advertisements.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Phonetics and social psychology studies explain these findings through biological differences in terms of pitch and factors like noise or perceived sensuality (Pennock‐Speck & del Saz Rubio, ). However, Martín‐Santana, Muela‐Molina, Reinares‐Lara, and Rodríguez‐Guerra () find no evidence for effectiveness differences related to the gender of the voice. Certain authors suggest that the higher level of confidence associated with the MV is based more on traditional stereotypes (Rodero et al, ; Whipple & McManamon, ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Phonetics and social psychology studies justify this fact by biological differences between voices along parameters such as fundamental frequency (F0, pitch) or format frequencies (Gélinas-Chebat, Chebat, & Vaninski, 1996). Researchers in advertising have carried out empirical comparisons of MV and FV and generally concluded that the MV may generate higher credibility, confidence, and expertise power and is therefore more persuasive than the FV (Martín-Santana, Muela-Molina, Reinares-Lara, & Rodríguez-Guerra, 2015). The work of Dolliver (2010), on the other hand, did not identify any differences in the persuasiveness of the gender.…”
Section: Theoretical Background and Hypothesismentioning
confidence: 99%